BAHASA DAN SENI SUNDA DI ERA GEN Z - Elis Suryani; Rangga Saptya Mohamad Permana (PT. RANESS MEDIA RANCAGE, 2025)
Every nation and even every ethnic group on Earth—possesses a culture that continually evolves in line with technological advances, the rapid growth of scientific knowledge, and the progression of time. Therefore, as the next generation, we must actively preserve, protect, and sustain our cultural heritage, particularly the customs, traditions, and ancestral legacies passed down from previous generations. These artistic elements should be preserved and further developed in the present day to prevent their extinction, especially in the domains of language and the arts. In the current Generation Z era, the acceleration of civilization and its supporting aspects is difficult to contain. If the younger generation shows indifference toward their own local linguistic and artistic wisdom, particularly that of Sundanese heritage, the current cultural wealth and diversity will gradually erode and may ultimately vanish. This is the motivation behind this study: to encourage Generation Z to become more familiar with, learn about, and actively engage in preserving Sundanese language and arts, so they are not lost to time. This study adopts a qualitative approach, utilizing descriptive-analytical methods through sociolinguistic, hermeneutic, and cultural studies frameworks. Hopefully, this work will provide valuable insights and contribute to other academic disciplines in a multidisciplinary manner